PENGATURAN HUKUM DAN DAMPAK PENGKAPLINGAN LIAR BAGI PEMBELI TANAH DI KOTA DENPASAR - Anggun Putrirosari, Birgita; Sujana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013, 2013)
The title of this research is “ The Law Regulation and Effect of Illegal Kaveling Toward Buyers of The Land in Denpasar”. The purpose of the research is to know the law regulation about land kaveling and the effect of Illegal Kaveling Toward Buyers of The Land in Denpasar. The method used is empirical method. The increasing of the number of citizens in Denpasar causes the increasing of residence in the city area. This phenomena causes the more kaveling and converted of farm land for residence illegay from the authority department that is from Land Consolidation Department and National Land Agency. Illegal kaveling has agreat impact toward the nature, that is decreasing farm land and green zone. However, it causes several bad effects toward the buyer of illegal kaveling land is not suitable with the purpose of the land usage, there is no suitable social facilities and public facilities with the government regulation, and furthermore, it is difficult to get the government help in relation with the development of social and public facilities quality.
Keywords: Illegal kaveling, Impact, land buyer